Comparison of intraoperative procedures for isolation of clinical grade stromal vascular fraction for regenerative purposes: a systematic review - Dongen, Joris A.; Tuin, A. Jorien; Spiekman, Maroesjka; Jansma, Johan; Lei, Berend; Harmsen, Martin C. (Journal of tissue engineering and regenerative medicine, 2018)
Intraoperative application of the stromal vascular fraction (SVF) of adipose tissue requires a fast and efficient isolation procedure of adipose tissue. This review was performed to systematically assess and compare procedures currently used for the intraoperative isolation of cellular SVF (cSVF) and tissue SVF (tSVF) that still contain the extracellular matrix. Pubmed, EMBASE and the Cochrane central register of controlled trials databases were searched for studies that compare procedures for intraoperative isolation of SVF (searched 28 September 2016). Outcomes of interest were cell yield, viability of cells, composition of SVF, duration, cost and procedure characteristics. Procedures were subdivided into procedures resulting in a cSVF or tSVF. Thirteen out of 3038 studies, evaluating 18 intraoperative isolation procedures, were considered eligible. In general, cSVF and tSVF intraoperative isolation procedures had similar cell yield, cell viability and SVF composition compared to a nonintraoperative (i.e. culture laboratory‐based collagenase protocol) control group within the same studies. The majority of intraoperative isolation procedures are less time consuming than nonintraoperative control groups, however. Intraoperative isolation procedures are less time‐consuming than nonintraoperative control groups with similar cell yield, viability of cells and composition of SVF, and therefore more suitable for use in the clinic. Nevertheless, none of the intraoperative isolation procedures could be designated as the preferred procedure to isolate SVF. Copyright © 2017 John Wiley & Sons, Ltd.